Moderating role of intellectual capital on capital structure and corporate performance of high technology industry in China and United States - Shiyu, Li (2023)
As one of the knowledge-intensive industries in today's knowledge-based economy, the high technology industry is becoming increasingly competitive. How to improve corporate performance is a key concern for most companies. Since the Modigliani-Miller (MM) Theorem was proposed, research on the relationship between capital structure and corporate performance has been a popular academic topic. At the same time, intellectual capital is the core resource of knowledge considered as one of the core capital forms of high-tech companies. Its importance in creating value and maintaining long-term competitive advantage for corporate becomes abundantly obvious. Therefore, it is of great practical significance to explore the relationship between capital structure and corporate performance of high-tech companies from the perspective of intellectual capital. The research background is based on the US-China trade war. Since high-tech industry is the most affected industry in this trade war, the sample is selected from the top 200 listed companies in high-tech industry with the highest market capitalization in two countries, totaling 400 companies. The balanced dataset employed in the study covers a period from the year 2017 to 2019 and semiannuals were used as a study period, so a total of six study periods. The data analysis consisted of two stages. The first stage is to calculate firm efficiency as a measure of corporate performance using the Data Envelopment Analysis (DEA). The second analysis step is to use the static panel regression analysis by Pooled Ordinary Least Square (POLS), Fixed Effect (FE), and Random Effect (RE) models. Subsequently, the Generalized Method of Moments (GMM) is adopted as a further robustness check test for the possibility of endogeneity in the models. The results of the study reveal a significant relationship between debt to asset and long-term debt to equity as important measures of capital structure and corporate performance. Furthermore, human capital efficiency and value added intellectual coefficient can both have a positive and significant impact on corporate performance. Moreover, the statistics indicate that intellectual capital has a significant moderating effect between capital structure and corporate performance. The study concludes that the capital structure and intellectual capital have significant impact on corporate performance. Furthermore, the study presents evidence on the moderating role of intellectual capital on the link between capital structure and corporate performance. The study contributes to the existing body of knowledge, empirical and practice. Firstly, this comparative research contributes in enlarging the existing literature on the relationship among capital structure and corporate performance of the high-tech industry in the economic context of the US-China trade war. Secondly, the using of Value Added Intellectual Coefficient (VAIC) to measure intellectual capital establishes a performance and intellectual capital evaluation index system that meets the characteristics of this type of enterprise, further laying the foundation of a certain knowledge system for the development of high-tech industry. Finally, the findings suggest that high-tech company managers should pay more attention to intellectual capital, so that intellectual capital can be employed efficiently and effectively and that the impact of capital structure on the company can be adjusted to better contribute to business operations.